Trajectories and Predictors of Symptom Occurrence, Severity, and Distress in Prostate Cancer Patients Undergoing Radiation Therapy - Knapp, Katie (2012)
CONTEXT: Radiation therapy (RT) is a common treatment for prostate cancer. Despite available research, prostate cancer patients report that information about side effects is their most important unmet need. Additional research is needed that focuses on specific dimensions of the patient’s symptom experience. OBJECTIVES: The study’s purposes were to evaluate the trajectories of occurrence, severity, and distress of the six most prevalent symptoms reported by patients undergoing RT for prostate cancer and to evaluate the effects of selected demographic and clinical characteristics on these trajectories. METHODS: Patients completed the Memorial Symptom Assessment Scale eleven times before, during, and after RT. For problems with urination, pain, lack of energy, feeling drowsy, difficulty sleeping, and diarrhea, the trajectories of occurrence, severity, and distress were evaluated using multilevel generalized linear models. RESULTS: Across all three dimensions, pain, lack of energy, feeling drowsy, and difficulty sleeping followed a decreasing linear trend. Problems with urination and diarrhea demonstrated more complex patterns of change over time. CONCLUSION: Although longitudinal data on pain, lack of energy, feeling drowsy, and difficulty sleeping are limited, they are highly prevalent symptoms in these patients. In addition, diarrhea becomes a significant problem for these patients over the course of RT. A number of demographic and clinical characteristics affects the trajectories of these common symptoms differentially.